Pengaruh Penggunaan Metode Eksperimen Terhadap Perkembangan Keterampilan Sains Anak Usia 5-6 Tahun Di TK GKPI Tarutung Kota - Lestari Sri Wahyuni Panjaitan; Julita Herawati P; Lasmaria Nami Simanungkalit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of the use of experimental methods on the development of science skills of children aged 5-6 years in GKPI Kindergarten Tarutung City. The research hypothesis is: "There is a significant influence between the use of experimental methods on the development of science skills of children aged 5-6 years in GKPI Kindergarten Tarutung City". The population was all children aged 5-6 years in GKPI Kindergarten Tarutung City totaling 113 students. The research sample was determined using a purposive sampling technique, namely 26 students of class B1 as the experimental class using the experimental method and 25 students of class B3 as the control class using the usual treatment (conventional class). This research method is a quantitative method with the type of Quasi Experimental Design using the Nonequivalent Control Group Design. The instrument used in this study was a questionnaire item of 15 items. The results of the data analysis show that the average N-Gain score in the experimental class is 0.8157, which falls into the high category, while the control class has an average score of 0.2129, which is in the low category. The results of the independent t-test show that tcount = 10.845 is greater than ttable = 2.021 (α = 0.05; df = 37.914). Thus, it can be concluded that the research hypothesis is accepted, namely there is a significant effect of using the experimental method on the development of science skills of children aged 5-6 years at TK GKPI Tarutung City, thus the null hypothesis (H0) which states that there is no significant effect is rejected.